A Comparative Analysis of Legal Frameworks for Investments in Africa by China and the European Union - Hügens, Jonathan (Department of Commercial Law, 2021)
This thesis presents a comparative analysis of the legal investment frameworks of the European Union and China in African countries. The thesis reviewed financial instruments of foreign direct investments, official development assistance and other official flows. The legal analysis focus on the demand on political conditions to access the financial assistance; under which conditions are the projects tendered; and which labor standards set the parties while the project is implemented. All reflected under the aspect of the fairest condition for African countries. The comparison figured out that the European Union with its demands for the implementation of human rights, democracy and the rule of law facing certain reluctance of most African governments for a full implementation while contrary to that the OneChina principle is broadly acknowledge by African governments to gain investments. When projects are tendered the research presents that the European Union searches for local and regional providers to strengthen African businesses. This with guidelines for core labor laws based on human rights when it comes to the implementation. While China tenders with a strong commercial self-interest and does not set any labor standards relaying on local laws and showing limited interest and understanding when it comes to implementation.